RAMI analysis of the ITER CIS - Kitazawa, Sin-iti; Okayama, Katsumi; Neyatani, Yuzuru; Sagot, Francois; van Houtte, Didier (Fusion engineering and design, 2014)
•We performed the functional analysis of the ITER CIS.•We performed a failure mode analysis of the ITER CIS.•We estimated the reliability and availability of the ITER CIS.•The ITER RAMI approach was applied to the ITER CIS for technical risk control in the design phase. ITER is the first worldwide international project aiming to design a device that proves the physics and technological basis for fusion power plants to produce nuclear fusion energy. In the project, the RAMI approach (reliability, availability, maintainability and inspectability) has been adopted for technical risk control to guide the design of components in preparation for operation and maintenance. RAMI analysis of the ITER central interlock system (CIS), which shall provide investment protection for the ITER systems was performed on the conceptual design. A functional breakdown was prepared in a bottom-up approach, resulting in the system being divided into 5 main functions and 7 sub-functions which are described using the IDEFØ method. Reliability block diagrams (RBDs) were prepared to estimate the reliability and availability of each function under stipulated operating conditions. Initial and expected scenarios were analyzed to define risk-mitigation actions. The inherent availability of the ITER CIS expected after implementation of mitigating actions was calculated to be 99.86% over 2 years, which is the typical interval of the scheduled maintenance cycles. A failure modes, effects and criticality analysis (FMECA) was performed to initiate risk mitigation action. Criticality matrices highlight the risks of the different failure modes with regard to the probability of their occurrence and impact on operations. It was assessed that the availability of the ITER CIS, with appropriate mitigating actions applied, meets the project availability requirement for the system.